EVALUATION OF DEVELOPMENT EFFICIENCY OF BRIGJEND SUDIARTO BUSINESS TOWARDS MOSQUITOON ON SIMPANG MODELING - Muhammad Teqi Wijaya; Kartono Wibowo (UNISSULA Semarang, 2018)
ABSTRACTThis research aims to examine the efficiency of Brigjend Soediarto fly over development towards the traffic jam in Pedurungan intersection. The approach conducted in this research is quantitative paradigm, with the quantitative method in the process of analysis. According to the analysis, the recent condition indicates high traffic flows density in each intersection. The level of service (LOS) in Brigjend Soediarto road is 1,421 in the F level. It is predicted that after the development of fly over, the level of service increasse into C with LOS = 0.579. Meanwhile, the LOS in Soekarno-Hatta road is 0.854 with the D level, and increases into B level with LOS = 0.226. While LOS Fatmawati road is 0.856 with the D level and increases into B with LOS=0.284. Before the development, the vehicle speed in Pedurungan intersection was 5.914 km/hour. After the development is is predicted that the vehice speed will be 49.885 km/hour. So that the average speed is 43.97 km/hour. Based on those analysis, the efficiency of the development of Brigjend Soediarto fly over is 76.28%. It can be concluded by the development of Brigjend Soediarto fly over, it is efficiently increasing the flow of traffic in Pedurungan intersection. Keywords : Brigjend Soediarto Fly Over, Pedurungan Intersection, Traffic Delay